Stimulus-Response Compatibility Effect in the Near-Far Dimension: A Developmental Study - Richez, Aurélien; Olivier, Gerard; Coello, Yann (Frontiers in Psychology, 2016)
The present study investigates the developmental aspect of stimulus-response compatibility effect in 8 to 11-years-old children. The task consisted in manually responding to the colour of a pawn presented on a chessboard at different distances. Manual responses were provided by reaching a proximal or distal location depending on the colour of the stimulus. We found that reaction time was affected by the conflict generated by the response suggested by the location of the stimulus and the response required according to its colour. This was not the case for movement time despite we found a higher rate of long duration movements in the incongruent than in the congruent spatial condition. The SRC effect was however observed in children older than 10 years old. These findings provide additional evidence for a reorganization of the perceptual system during the period of 8 to 10 years, integrating progressively multimodal information and preparing more efficiently the body to act in the environment.